A synthesis of concepts of resilience to inform operationalization of health systems resilience in recovery from disruptive public health events including COVID-19 - McDarby, Geraldine; Seifeldin, Redda; Zhang, Yu; Mustafa, Saqif; Petrova, Mila; Schmets, Gerard; Porignon, Denis; Dalil, Suraya; Saikat, Sohel (Frontiers in Public Health, 2023)
This article is part of the Research Topic ‘Health Systems Recovery in the Context of COVID-19 and Protracted Conflict’ Health systems resilience has become a ubiquitous concept as countries respond to and recover from crises such as the COVID-19 pandemic, war and conflict, natural disasters, and economic stressors inter alia. However, the operational scope and definition of health systems resilience to inform health systems recovery and the building back better agenda have not been elaborated in the literature and discourse to date. When widely used terms and their operational definitions appear nebulous or are not consistently used, it can perpetuate misalignment between stakeholders and investments. This can hinder progress in integrated approaches such as strengthening primary health care (PHC) and the essential public health functions (EPHFs) in health and allied sectors as well as hinder progress toward key global objectives such as recovering and sustaining progress toward universal health coverage (UHC), health security, healthier populations, and the Sustainable Development Goals (SDGs). This paper represents a conceptual synthesis based on 45 documents drawn from peer-reviewed papers and gray literature sources and supplemented by unpublished data drawn from the extensive operational experience of the co-authors in the application of health systems resilience at country level. The results present a synthesis of global understanding of the concept of resilience in the context of health systems. We report on different aspects of health systems resilience and conclude by proposing a clear operational definition of health systems resilience that can be readily applied by different stakeholders to inform current global recovery and beyond.